A role for accelerometry in the differential diagnosis of tremor syndromes - Bove, Francesco (Funct Neurol, 2018)
Accelerometry is a reliable tool for gauging the occurrence, amplitude and frequency of tremor. However, there is no consensus on criteria for accelerometric diagnosis of tremor syndromes. We enrolled 20 patients with essential tremor (ET), 20 with dystonic tremor (DT), and 20 with classic parkinsonian tremor (PD-T), all meeting accepted clinical criteria. All the patients underwent dopamine transporter imaging (by means of single-photon emission computed tomography) and triaxial accelerometric tremor analysis. The latter revealed groupwise differences in tremor frequency, peak dispersion, spectral coherence, unilaterality and resting vs action tremor amplitude. From the above, five diagnostic criteria were extrapolated for each condition. Receiver operating characteristic curves, depicting criteriabased scoring of each tremor type, showed negligible declines in specificity for scores ≥4 in patients with ET or DT and scores ≥3 in patients with PD-T, thus providing a simple scoring method (accelerometrically derived) for differential diagnosis of the principal tremor syndromes.